Extração seletiva e pré-concentração de cromo (III) em amostras aquosas por extração em ponto nuvem - Acevedo, Maria Soledad Moura Soares Fernández (2014)
This work, a procedure for separation and preconcentration of chromium (III) by cloud point extraction and determination by flame atomic absorption spectrometry in mineral water samples was developed. This procedure is based on the formation of the complex of Cr(III) with PAN (1-(2- pyridylazo) 2-naphthol) in the presence of buffer solution of pH 11 and 0.05 % (w/v) Triton X-114 as surfactant. The variables that affect the complex formation, extraction and separation of the phases, such as the concentration of complexing and surfactant agents, the effect of pH and volume of buffer solution were evaluated. An electrolyte solution of NaCl was used to conduce the point cloud formation without the need for heating. From the optimized conditions for determination of Cr(III), detection limit of 0.47 mg L-1, limit of quantification of 1.56 mg L-1 relative standard deviation (RSD) of 3.05 % for n = 10 and enrichment factor of 20.3 were obtained. The accuracy was proved by standard addition and recovery experiments, obtaining quantitative recoveries in the range 88-120%, and the method was applied to samples of mineral water.